The bridging of private and public housing and enhancement of government legitimacy in Singapore. - Ng, Sing Hui. (2011)
The aim of this paper is to provide an insight on how the State manages public housing in Singapore, in view of the increasing aspirations of the burgeoning middle class. By focusing on the Design, Built and Sell Scheme (DBSS) as well as the Executive Condominiums (ECs), I attempt to analyze how the bridging of private and public housing is studied through three aspects – ideological, price as well as the physical factors. More importantly, through these housing developments, I shall study how the state uses housing as a political tool to enhance its legitimate authority in Singapore.